HUBUNGAN VARIABILITAS GLIKEMIK DENGAN INGKAT KEPARAHAN KLINIS PASIEN STROKE SKEMIK DI RSUD ULIN BANJARMASIN - Muhammad Ervin; Fakhrurrazy Fakhrurrazy; Triawanti Triawanti (Homeostasis, 2019)
Abstract: Stroke is a state of sudden loss of brain function resulting from a disruption in the cerebral blood supply with symptoms lasting at least 24 hours or resulting in death. This study aims to analyze the relationship between glycemic variability and the clinical severity of ischemic stroke patients in Ulin Hospital Banjarmasin. This study was observational analytic with cohort design. The population in this study were all patients diagnosed with ischemic stroke in Ulin Banjarmasin Hospital in August-November 2018. The patient's glycemic variability value will be obtained by determining the mean and standard deviation of the patient's glycemia levels taken for 7 days and the patient's clinical value by using the National Institute Health of Stroke Scale (NIHSS) questionnaire on the first day and day 7 the patients were hospitalized. The sample size for this study is 30 people. The results of this study were that the incidence of ischemic stroke was found to occur most in the age group> 45 years (96.7%), and in patients with hypertension (76.7%). The results of bivariate analysis showed that the glycemic variability variable had a significant correlation with the patient's clinical variable (R = 0.767 **). The conclusion of this study is that there is a relationship between glycemic variability and the clinical severity of ischemic stroke patients in Ulin Hospital Banjarmasin Keywords: ischemic stroke, glycemic variability, National Institute Health of Stroke Scale (NIHSS)  Abstrak: Stroke adalah keadaan hilangnya fungsi otak secara tiba-tiba akibat dari gangguan pada suplai darah serebral dengan gejala yang berlangsung minimal 24 jam atau mengakibatkan kematian. Penelitian ini bertujuan untuk menganalisis hubungan antara variabilitas glikemik dengan tingkat keparahan klinis pasien stroke iskemik di RSUD Ulin Banjarmasin. Penelitian ini bersifat observasional analitik dengan desain cohort. Populasi pada penelitian ini adalah semua pasien yang didiagnosis stroke iskemik di RSUD Ulin Banjarmasin pada bulan Agustus-November 2018. Nilai variabilitas glikemik pasien akan didapat dengan menentukan mean dan standar deviasi dari kadar glikemia pasien yang di ambil selama 7 hari dan klinis dari pasien akan dinilai dengan menggunakan kuisioner National Institute Health of Stroke Scale (NIHSS) pada hari pertama dan hari ke-7 pasien di rawat inap. Besar sampel pada penilitan ini adalah 30 orang. Hasil dari penelitian ini adalah kejadian stroke iskemik ditemukan paling banyak terjadi pada kelompok usia >45 tahun (96,7%), dan pada penderita hipertensi (76,7%). Hasil analisis bivariat menunjukkan bahwa variabel variabilitas glikemik memiliki korelasi yang signifikan dengan variabel klinis pasien (p=0,00) dan (r=0,767**). Kesimpulan dari penelitian ini adalah terdapat hubungan antara variabilitas glikemik dengan tingkat keparahan klinis pasien stroke iskemik di RSUD Ulin Banjarmasin. Kata-kata kunci: Stroke iskemik, variabilitas glikemik, National Institute of Health Stroke Scale (NIHSS)